Management of inverted papilloma with degloving approach - Farhat dr (Majalah Kedokteran Nusantara The Journal Of Medical School, 2013)
According to the World Health Organization, inverted papilloma is defined as a benign epithelial tumor composed of well-differentiated columnar or ciliated respiratory epithelium having variable squamous differentiation. A 62 years old man came into Adam Malik Hospital on April 19th, 2013 with complaint of unilateral nasal obstruction for 5 years. After examinations we diagnosed the patient with inverted papilloma and performed degloving approach to to removed the tumor dand the tumor removed intact succesfully. Inverted papilloma is one of the sinonasal papilomas subtype which aggresively treated because of a relatively high recurrence rate and potential for malignant transformation.Keywords : inverted papilloma; sinonasal; degloving